“Teach me to pray”: the prayerological structure of the novel Anna Karenina of L.N. Tolstoy in the context of Christian Revival in the last half of 19th century (ENTHYMEMA, 2020)
The role of prayers in the themes of Anna Karenina is considered. It is noted that Leo Tolstoy typology of characters is based on their attitude to prayers and praying. The paper analyzes origins and textual parallels of Levin’s prayers on the background of Christian revival in Russia during Alexander II’s reign, as well as certain aspects of Tolstoy prayerology (i.e. theology and theory of prayer, concept of prayer).
Keywords: Lev Tolstoy; Anna Karenina; Konstantin Levin; prayer; Henry Suso